Visuomotor cuing through tool use in unilateral visual neglect. - Forti, S; Humphreys, G (2004)
In the present study, the authors examined the effect of tool use in a patient, MP, with neglect of peripersonal space. They found that target detection improved when the patient searched with his arm outstretched, when both visual and motor cues were present. Motor cues (arm outstretched but hidden from view) and visual cues alone (shining a torch on the objects) were less effective. In a final experiment, the authors reported that MP established a better memory for the objects that were searched for when a combined visual and motor cue was present. The authors argue that search was improved by combined visuomotor cuing, which was effective when the action could affect the objects present. Visuomotor cuing also led to stronger memories for searched locations, which reduced any tendency to reexamine positions that had been searched previously. The data are discussed in terms of the interaction between perception and action.